A study on the quality and shelf life of ripening mango using the PCM-based solar cold storage system. Issue 1 (31st December 2022) - Sarafoji, P.; Mariappan, Vairavan; Anish, R.; Karthikeyan, K.; Babu, N.
Abstract : In this work, a phase change material (PCM)-based prototype solar cold storage (PSCS) system was developed to investigate the effect of shelf life of fresh post-harvested ripening mango and the performance of the PCM-based PSCS system. The experimental studies were conducted in two different storage conditions such as atmospheric and PCM-based PSCS systems. The experimental results showed significant reduction of weight about 50–10% at the end of second week at ambient conditions and PCM-based PSCS system, respectively. A firmness is noticed about 14–15 N at the end of the second week in cold storage mangoes, and in atmospheric storage it was about 6 N. Total soluble solids increased gradually from 6% to 18% during experimentation in cold storage and rapidly varied after fourth day in atmospheric storage. Furthermore, a slight decrement was found in the titratable acidity within the permissible limit in cold storage mangoes.